Prevalence, Awareness, and Control of Arterial Hypertension in a Russian Population. The Ural Eye and Medical Study - Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Zainullin, Rinat M.; Salavatova, Venera F.; Gilmanshin, Timur R.; Yakupova, Dilya F.; Uzianbaeva, Yulia V.; Arslangareeva, Inga I.; Panda-Jonas, Songhomitra; Mukhamadieva, Svetlana R.; Khikmatullin, Renat I.; Aminev, Said K.; et al. (Frontiers in Public Health, 2020)
Background: To investigate prevalence and awareness of arterial hypertension in Russia. Methods: The population-based Ural Eye and Medical Study, performed in an urban and rural region in the Russian republic Bashkortostan, included 5891 (80.5%) individuals aged 40+ years out of 7328 eligible individuals. The participants underwent a detailed interview and medical examination. Arterial hypertension was defined using the criteria defined by the American College of Cardiology/American Heart Association. Results: The prevalence of normal blood pressure (BP), elevated BP, hypertension stage 1, stage 2 and hypertensive crisis was 750/5891 (12.7%;95% confidence interval (CI):4.7,5.9), 312/5891 (5.3%;95%CI:4.7,5.9), 2187/5891 (37.1%;95%CI:35.9,38.4), 2484/5891 (42.2%;95%CI:40.9,43.4), and 158/5891 (2.7%;95%CI:2.3,3.1), respectively. The overall prevalence of elevated BP/hypertension was 5141/5891 (87.3%;95%CI:86.4,88.1). Awareness of elevated BP/hypertension was 2289/5223 (45.4%;95CI:44.0,47.0). Among 1055 (20.2%;95%CI:19.1,21.3) individuals under anti-hypertensive treatment, 33 (3.1%) individuals had normal BP values. Higher prevalence of elevated BP/hypertension was associated with older age (P<0.001;odds ratio (OR):1.04;95%CI:1.03,1.05), male gender (P<0.001;OR:2.56;95%CI:2.10,3.16), urban region (P=0.01;OR:1.26;95%CI:1.05,1.51), lower educational level (P=0.003;OR:0.92;95%CI:0.87,0.97), higher body mass index (P<0.001;OR:1.15;95%CI:1.12,1.18), higher waist-hip circumference ratio (P=0.003;OR:6.16;95%CI:1.89,20.0), higher prevalence of sitting or reclining for more than 18 hours per week (P=0.003;OR:1.33;95%CI:1.10,1.61), higher prevalence of alcohol consumption (P<0.001;OR:1.61;95%CI:1.27,2.05), and higher serum concentrations of triglycerides (P=0.01;OR:1.22;95%CI:1.05,1.43) and glucose (P<0.001;OR:1.15;95%CI:1.07,1.24). Using the former definition of hypertension (systolic BP≥140mmHg and/or diastolic BP≥ 90mmHg), the prevalence of hypertension was 3134/5891 (53.2%;95%CI:51.9,54.5). Conclusions: Using the new definition of arterial hypertension, the prevalence of elevated BP/hypertension in a typically mixed Russian population aged 40+ years was high (87.3%), with an awareness rate of 45.4% and treatment rate of 20.2%. The rate of therapeutic control of BP elevation in the individuals under treatment was less than 5%.